Digital Transformation, Procurement Capability, and Competitive Advantage : The Mediating Role of Procurement in Turbulent Markets - Safira Meisya Pramudhita; Ratih Hendayani (International Journal of Management and Business Applied, 2026)
This study aims to analyze the influence of digital transformation on the procurement process in order to drive the achievement of competitive advantage, by taking into account the factors of multi-supplier, digital capabilities, and market turbulence in Telkomsigma. This study employs a quantitative and explanatory approach to examine the relationships between variables. Hypothesis testing is conducted using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS) using SmartPLS. The results show that digital transformation has a positive effect on procurement, procurement has a positive effect on competitive advantage, and procurement plays a significant mediating role between digital transformation and competitive advantage. In addition, multi-supplier strategies positively influence digital capabilities, and market turbulence positively affects competitive advantage. However, digital transformation, multi-supplier, and digital capabilities do not have a significant direct effect on competitive advantage. Lastly, digital capability does not have a significant mediating role between multi-supplier and competitive advantage. This study contributes to the procurement literature by highlighting the implementation of digital transformation and multi-supplier approaches to enhance competitive advantage in highly turbulent markets. It also provides recommendations for advancing digitalization and strengthening digital capabilities in procurement processes and optimizing the role of procurement functions.